Study On Consumer Behaviour: What Motivates Malaysian To Patronize International Franchise Coffee Shop (International Cafe) Than Local Coffee Shop (Local Cafe) - Yeoh, Soo Leng (2006)
The purpose of this dissertation is to discuss on the observable behaviours, such as the amount purchased, and when , with whom, by whom and how purchases are consumed. It also includes non-observable variables, such as consumers' values, personal needs and perceptions, what information they have in memory, how they obtain and process information, how they evaluate alternatives, and how they feel about the ownership and use of various products.